Pemberdayaan UMKM Melalui Pemasaran Digital - Arifa, Amalia Beladinna; Wibowo, Fahrudin Mukti; Alika, Shintia Dwi; Burhanuddin, Auliya; Adhitama, Rifki; Paradise, Paradise (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
In the digital era, the use of information technology has become a key factor in business development, especially for Micro, Small, and Medium Enterprises (MSMEs). This community service program focuses on providing training and mentoring in digital marketing for MSMEs in Brani Village, Cilacap Regency. The program aims to enhance participants’ understanding and skills in utilizing social media platforms, particularly Instagram, to promote local products such as cassava chips, salted eggs, and peyek. The training covers basic digital marketing concepts, content creation strategies, and methods to increase audience engagement. Despite facing challenges like limited digital literacy and infrastructure, the program succeeded in improving participants’ ability to create engaging content and manage online business accounts. This initiative is expected to empower MSMEs to expand their market reach and increase competitiveness through digital transformation.